Rating functional costs of key training tools for junior sprinters - Nikitushkin, V. G.; Cherkashin, V. P.; Chesnokov, N. N.; Zuev, S. N. (Theory and Practice of Physical Culture, 2018)
Active team sports are underemployed by the sport practices today albeit they deserve more attention. Moreover, they are still undervalued by many sport practitioners for a variety of reasons including their poor knowledge of potential training benefits of team sports; reservations as to the team sports efficiency; and inadequate experience in applying the relevant game tools. Objective of the study was to develop a speed- and speed-strength-building method for the 12-16 year-old sprinters with application of active team sports and game exercises. Applied for the study purposes were the following methods: analysis of the available literature on the subject; educational process tests; questionnaire survey; educational experiment; and standard mathematical methods of statistics. The study was performed in the period of 2012-2017 in the indoor and outdoor training conditions and in laboratory, with more than 100 junior sprinters being subject to the study.